1996
DOI: 10.1016/s1078-5884(96)80270-x
|View full text |Cite
|
Sign up to set email alerts
|

Biological responses differ considerably between endovascular and conventional aortic aneurysm surgery

Abstract: Endovascular aortic aneurysm repair induced a significant inflammatory response, mainly involving TNF-alpha and differing from the findings during open AAA repair. These inflammatory responses were probably related to blood pressure decreases during the procedures. On the other hand, conventional repair induced responses related to the more extensive surgical trauma and reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
3
15

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 21 publications
4
57
3
15
Order By: Relevance
“…This indicates that the presence of the thrombus in the isolated aneurysm sac does not induce thrombin production as previously suggested. 20,29 The significant increase in TAT at 24 hours postoperatively may be explained by increased binding with antithrombin III in response to manipulation during insertion of the stent graft. Shimazaki et al 18 and Monaco et al 21 showed a significant reduction in antithrombin III and a significant increase in TAT on the first postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the presence of the thrombus in the isolated aneurysm sac does not induce thrombin production as previously suggested. 20,29 The significant increase in TAT at 24 hours postoperatively may be explained by increased binding with antithrombin III in response to manipulation during insertion of the stent graft. Shimazaki et al 18 and Monaco et al 21 showed a significant reduction in antithrombin III and a significant increase in TAT on the first postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] However, some authors have reported that EVAR promotes a systemic inflammatory response and prothrombotic coagulopathy equal if not greater than that witnessed after open surgical repair. 19,20 It has been hypothesized that this is secondary to cytokine release from thrombus within the aneurysm sac either as a result of introducer and catheter manipulation or, possibly, ischemia after AAA exclusion. 19,21 The presence of type II endoleaks may allow these moieties to reach the systemic circulation and cause their deleterious effects.…”
mentioning
confidence: 99%
“…19,20 It has been hypothesized that this is secondary to cytokine release from thrombus within the aneurysm sac either as a result of introducer and catheter manipulation or, possibly, ischemia after AAA exclusion. 19,21 The presence of type II endoleaks may allow these moieties to reach the systemic circulation and cause their deleterious effects. The use of contrast media has also been reported to induce arterial endothelial damage, and this may also be relevant to the development of what has been termed "postimplantation syndrome" after EVAR.…”
mentioning
confidence: 99%
“…It is known that IL-6 levels have been most commonly found to correlate with the degree of inflammatory insult, including the duration of surgery and the extent of surgical dissection [17,35]. Likewise, IL-8 concentrations have been shown to correlate with the severity of tissue injury and elevations of plasma IL-8 concentrations often appear simultaneously with increases in plasma IL-6 levels [27][28][29].…”
Section: Discussionmentioning
confidence: 99%